Integrating the perspectives of relevant stakeholders into the development of a service robot for nursing homes: needs analysis and scenario development using the International Classification of Functioning, Disability and Health (ICF) - Horstmannshoff, Caren; Jahn, Eva Theresa; Müller, Martin (International Journal of Social Robotics, 2025)
The demand for nursing home care is expected to increase. Robotic systems are discussed to address the nursing workforce shortage and maintain the quality of care by taking over service tasks. The KoBo34 project aimed to develop a service robot for nursing home care. A key aspect of successful robot development is to involve all potential future users. This paper presents an example of integrating identified nursing home residents’ needs from the perspective of relevant stakeholders into developing the service robot. A needs analysis was conducted through semi-structured interviews and field observations involving residents, their relatives, nursing home staff, and community-dwelling seniors. Data was analysed by structured qualitative content analysis using the International Classification of Functioning, Disability and Health. The identified needs were discussed regarding technical feasibility and safety and consented in a panel. User stories were derived and combined into three scenarios, forming the framework for the robot’s technical development. Through ten group and 13 individual interviews with 71 participants and 16 field observations, we identified Needs for support and Wishes and Doubts regarding technology. Inductive categories were doubts about Individuality, Substitution of caregivers through technology, and Data protection and privacy. The needs analysis revealed that residents often need help transporting trays, crave additional snacks between meals or after dinner, frequently forget to drink and cannot reach the in-house store. Based on structured discussions among the researchers and validation from nursing home staff, three scenarios were developed: Serving and clearing plates, offering beverages and snacks and supporting with shopping.
Gesehen am 16.10.2025